The Evaluation of Vaginal Hysterectomy Using Spinal Anaesthesia - Ibnu Pranoto, Ibnu Pranoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background. Vaginal hysterectomy can be performed on patient under general or spinal anesthesia. There are some advantages of spinal anesthesia compared to general anesthesia, although some prefer general anesthesia. We have done frequently vaginal hysterectomy using spinal anesthesia and we are reporting our experience.Objective:To know the spinal anethesia efficency compared to general anesthesia in terms of duration of vaginal hysterectomy operation, amount of bleeding and length of stay.Design: Cross sectional descriptive studySetting: Sardjito HospitalMaterials and methods: Patients underwent vaginal hysterectomy in Dr. Sardjito Hospital from March 2005 until February 2007Results: 50 patients underwent vaginal hysterectomy that consisted of 44 patients with spinal anesthesia and 6 patients with general anesthesia. Vaginal hysterectomy with spinal anesthesia had shorter duration of operation (1.93 hours) compared to general anesthesia (1.95 hours). Patients length of stay was shorter with spinal anesthesia (5.8 days) compared to general anesthesia (9 days). The average amount of blood loss in spinal anesthesia was (250.34 mil compared to general anesthesia (625.0 mil.Conclusion: This study suggests that spinal anesthesia reduces length of hospital stay and amount of blood loss in patients with vaginal hysterectomy compared to general anesthesiaKey Words: vaginal hysterectomy, spinal anesthesia, general anesthesia, duration of operation, amount of bleeding and length of stay.